Mg–Sr–Nd Isotopic Insights into Petrogenesis of the Xiarihamu Mafic–Ultramafic Intrusion, Northern Tibetan Plateau, China. (7th January 2021) - Chen, Lie-Meng; Song, Xie-Yan; Hu, Rui-Zhong; Yu, Song-Yue; Yi, Jun-Nian; Kang, Jian; Huang, Kang-Jun
Abstract: To characterize the integrated magmatic processes for magma plumbing systems from mantle sources to magma chambers, we present Mg–Sr–Nd isotopic data for a representative mafic–ultramafic intrusion in Xiarihamu, northern Tibetan Plateau, China. The intrusion hosts the largest magmatic Ni–Cu sulfide deposit in an orogenic setting in the world and is composed predominantly of harzburgite, orthopyroxenite, websterite, and gabbronorite. The cumulate harzburgites have relatively low δ 26 Mg of orthopyroxene (–0·49 to –0·34‰) and moderately high ( 87 Sr/ 86 Sr)i and positive εNd ( t ) values (0·7067–0·7080 and +0·4 to +1·8, respectively). Most of the orthopyroxenites, websterites, and gabbronorites have slightly higher δ 26 Mg of orthopyroxene (–0·34 to –0·21‰) and higher ( 87 Sr/ 86 Sr)i and lower εNd ( t ) values (0·7087–0·7118 and –4·0 to –1·4, respectively) than the harzburgites. On the other hand, marginal facies (i.e. a few centimeters to meters from the contact between the intrusion and country rocks of schist, gneiss, and marble) including websterite and gabbronorite are marked by low δ 26 Mg of orthopyroxene (–0·44 to –0·33‰) and extremely high ( 87 Sr/ 86 Sr)i and negative εNd ( t ) values (0·7127–0·7172 and –5·4 to –4·8, respectively). The relatively low δ 26 Mg, moderately high ( 87 Sr/ 86 Sr)i, and positive εNd ( t ) of the harzburgites are best interpreted by inheritance from the mantle source, which was previously metasomatized by subducted Mg-rich carbonates. Given the fact that the solidus of carbonated mantle is significantly lower than that of volatile-free mantle, mantle metasomatism by carbonates may be critical to generate voluminous mafic magmas and to form the giant Xiarihamu Ni–Cu deposit and other magmatic sulfide deposits in convergent settings worldwide. The relatively high δ 26 Mg, high ( 87 Sr/ 86 Sr)i, and low εNd ( t ) of most orthopyroxenites, websterites, and gabbronorites were produced by extensive contamination of isotopically heavy crustal rocks in a deep-seated magma chamber. The slightly low δ 26 Mg, extremely high ( 87 Sr/ 86 Sr)i and negative εNd ( t ) of the marginal facies, compared with other websterites and gabbronorites, were governed by assimilation of local low-δ 26 Mg country rocks (e.g. gneiss and marble) at the Xiarihamu magma chamber during emplacement. These observations indicate that mafic–ultramafic cumulates away from marginal facies can preserve their primitive Mg–Sr–Nd isotope signatures inherited from deep magma chambers, even from mantle sources, with negligible crustal contamination during magma ascent and emplacement. These findings for the first time, to our knowledge, provide observational evidence to characterize the integrated magmatic processes of a single magma plumbing system from deep mantle source to magma chambers, which sheds light on the petrogenesis and mineralization of mafic–ultramafic intrusions.